The Role of Edge Computing in Enhancing IoT Systems Performance - Winslow, Liora (Journal of Computer Science and Software Applications, 2025)
Edge computing is emerging as a critical technology to address the limitations of cloud-centric architectures in IoT systems. By processing data closer to the source, edge computing reduces latency, enhances real-time data analysis, and alleviates network congestion. This paper explores the architectural framework of edge computing, its integration with IoT ecosystems, and the performance enhancements it delivers. Key applications, challenges, and future research directions are also discussed.